Are remittances inducing laziness in households? a reexamination of the evidence - Ducanes, Geoffrey M. ([Quezon City] School of Economics, University of the Philippines, 2012)
This study reexamines the available evidence on the often-repeated claim that international migration of a household member and the resulting remittances typically lead to laziness in the receiving households. The study finds, after replicating previous studies and testing the claim using more recent data, that there is in fact weak or no evidence to support such claim.
Title was 'Philippine Review of Business and Economics' until 1979. Title changed to 'Philippine Review of Economics and Business' from 1980-2000, and again changed to 'Philippine Review of Economics' since 2001.
Includes bibliographical references (page 19)
Keywords: Emigrant remittances -- Philippines -- Social aspects; Emigrant remittances -- Philippines -- Cost-of-living adjustments; Employment in foreign countries -- Social aspects; Households -- Philippines -- Social aspects